Periodontal Status and Quality of Life in Adult Patients Attending a Tertiary Care Centre in Kathmandu Valley - Shakya, Sonika; Shrestha, Priti; Poudel, Sabina (Journal of Nepalese Society of Periodontology and Oral Implantology, 2019)
Introduction: Symptoms of periodontal disease like redness, bleeding on brushing, loosening of affected teeth, and persistent bad breath are not usually documented in a research report. Such symptoms are highly relevant from the patient’s point of view and often have a considerable adverse impact on their daily quality of life.Objective: The objective of this study was to assess the periodontal health status and its impact on quality of life.Methods: Clinical attachment loss of total 100 participants were measured at six sites of all teeth and patients divided into severity groups according to loss of attachment. The Nepalese version of the Oral Health Impact Profile (OHIP-14) was used to assess impact of periodontal status on patient’s quality of life. In addition, participants were also asked to complete a simple ‘yes/no’ checklist of symptoms relating to their periodontal health in the past year which included swollen gums, sore gums, receding gums, loose teeth, drifting teeth, bad breath, or toothache.Results: Overall OHIP-14 score significantly differed between patient groups. The impact of oral health on quality of life was greater in patients with high/severe periodontitis and the result was statistically significant (p=0.001).Conclusion: There is significant difference between oral health related quality of life in healthy and periodontally involved patients as assessed by using OHIP-14. Treatment strategies should focus on improving the quality of life of periodontal patients.